An empirical examination of debt covenant restrictions and accounting-related debt proxies - Duke, Joanne C; Hunt, Herbert G (Journal of Accounting and Economics, 1990)
Prior studies of discretionary accounting choices have generally relied on one or more proxy variables to measure closeness to debt covenant restrictions without actually examining the existence or extent of restrictive covenants. This study tests the validity of the most commonly used proxy, the debt–equity ratio, by examining its relation to actual debt covenant restrictions for a random sample of U.S. firms. The results indicate that several versions of the debt–equity ratio capture the existence and tightness of retained earnings restrictionsand the existence of net tangible asset and working capital restrictions, but are unrelated to four other covenant restrictions.